Oestrogen Activates the MAP3K1 Cascade and β-Catenin to Promote Granulosa-like Cell Fate in a Human Testis-Derived Cell Line - Melanie K. Stewart (International Journal of Molecular Sciences, 2021)
Sex determination triggers the differentiation of the bi-potential gonad into either an ovary or testis. In non-mammalian vertebrates, the presence or absence of oestrogen dictates gonad differentiation, while in mammals, this mechanism has been supplanted by the testis-determining gene SRY. Exogenous oestrogen can override this genetic trigger to shift somatic cell fate in the gonad towards ovarian developmental pathways by limiting the bioavailability of the key testis factor SOX9 within somatic cells. Our previous work has implicated the MAPK pathway in mediating the rapid cellular response to oestrogen. We performed proteomic and phosphoproteomic analyses to investigate the precise mechanism through which oestrogen impacts these pathways to activate β-catenin—a factor essential for ovarian development. We show that oestrogen can activate β-catenin within 30 min, concomitant with the cytoplasmic retention of SOX9. This occurs through changes to the MAP3K1 cascade, suggesting this pathway is a mechanism through which oestrogen influences gonad somatic cell fate. We demonstrate that oestrogen can promote the shift from SOX9 pro-testis activity to β-catenin pro-ovary activity through activation of MAP3K1. Our findings define a previously unknown mechanism through which oestrogen can promote a switch in gonad somatic cell fate and provided novel insights into the impacts of exogenous oestrogen exposure on the testis.